Petros Konstantinidis (1864-1913) - KARDOULIS (Α.Γ. ΚΑΡΔΟΥΛΗΣ) A. G. (Journal of the Hellenic Veterinary Medical Society, 2017)
This biographical article has been edited with regard to the commemoration of eighty years since the BalKan Wars of 1912-1913 and in the memory of Petros Konstantinides (P.Κ.), reserve major of the Veterinary Corps, who was the only known casualty of the V.C. during these wars. P.K., diplomate of the Royal Military Veterinary School of Vienna, was a pioneer of the private exercise of the veterinary profession in Athens and contributed, with the booklets that he had edited, to the raising of the level of the veterinary care and animal welfare in this country. It is noteworthy that at that time there was not a Veterinary School in Greece and the only Veterinary Service existing was the military one.